The payback - Cauley, Kashana (Atria Books, an imprint of Simon & Schuster LLC, 2025)
"Jada Williams is good at judging people by their looks. From across the mall, she can tell not only someone's inseam and pants size, but exactly what style they need to transform their life. Too bad she's no longer using this superpower as a wardrobe designer to Hollywood stars, but for minimum wage plus commission at the Glendale mall. When Jada is fired yet again, she is forced to outrun the newly instated Debt Police who are out for blood. But Jada, like any great antihero, is not going to wait for the cops to come kick her around. With the help of two other debt-burdened mall coworkers, she hatches a plan for revenge. Together the three women plan a heist to erase their student loans forever and get back at the system that promised them everything and then tried to take it back"--